Characterization of green tea from banaba (Lagestromea speciosa) and ampalaya (Momordica charantia) leaves - Maquiling, Irene Reboquio (School of Technology, U.P. Visayas, 2006)
Five formulations of banaba-ampalaya tea were prepared by varyng the combination of dried banaba-ampalaya leaves such as 80% banaba - 20% ampalaya (formulation A); 85% banaba - 15% ampalaya (formulation B); 90% banaba - 10 % ampalaya (formulation C); 95% banaba - 5% ampalaya (formulation D) ; and 100% banana (formulation E).